Easy-to-use clinical measures of walking ability in children and adolescents with cerebral palsy: a systematic review. Issue 10 (8th May 2017) - Himuro, Nobuaki; Abe, Hirokazu; Nishibu, Hisato; Seino, Tsugumi; Mori, Mitsuru
Abstract: Objective: The aims of this systematic review were to identify quick, simple and easy-to-use measures of walking ability currently used to assess children and adolescents with cerebral palsy (CP), and to evaluate the clinical utility and psychometric properties of these measures. Data sources: The PubMed, CINAHL, SPORTDiscus and MEDLINE databases were searched up to March 2015. Review methods: Two independent reviewers rated the methodological quality of the identified measures using the COnsensus-based Standards for the selection of health status Measurement INstruments (COSMIN) checklist. Results: The 1-Minute Walk Test, Timed Up and Go Test, ABILOCO-Kids, Gillette Functional Assessment Questionnaire and Functional Mobility Scale were identified. Each measure can be carried out within 5 min with limited equipment, and does not require examiner training. There was "limited" to "strong" evidence on the reliability and validity of these measurements, whereas evidence on measurement error and responsiveness was limited. Conclusion: The identified measures in this systematic review may be considered for the clinical measurement of walking ability in children and adolescents with CP in a quick, simple and easy-to-use manner. However, there is overall a lack of evidence on the psychometric properties of these tools. The lack of evidence regarding measurement error and responsiveness might limit their value in measuring change over time. Implications for Rehabilitation: The ABILOCO-Kids, 1-Minute Walk Test, Timed Up and Go Test, Gillette Functional Assessment Questionnaire, Functional Mobility Scale can be performed within 5 min with limited equipment, and do not require examiner training for measuring of walking ability in children and adolescents with cerebral palsy. The clinicians should use these measurement tools carefully when assessing change over time as the available evidence on measurement error and responsiveness is limited. When clinicians use these measurement tools, the psychometric properties reported in this systematic review should be considered in the selection of tools and subsequent interpretation of results.